Clinical management of adolescents and young adults suffering from sarcoma in the French Rhône-Alpes region: A prospective exhaustive cohort with 10 years follow up. Issue 7 (July 2020) - Marec-Bérard, P.; Aho, S.; Berger, C.; Plantaz, D.; Aho-Glelé, L.S.; Ducimetière, F.; Duclos, A.; Fontanière, B.; Collard, O.; Blay, J.Y.; Sunyach, M.P.; Chotel, F.; et al.
Abstract: Introduction: Survival of adolescents and young adults (AYA) with sarcoma is lower than in younger patients. The objective of this study was to describe the regional healthcare circuits, the differences in the management between adult, paediatric and mixed units and to assess the prognostic impact of compliance with clinical practice guidelines (CPGs) on overall survival (OS) and on relapse free survival (RFS). Materials and methods: Retrospective analysis of the management and long term follow-up of all 13–25 year old patients with a sarcoma diagnosed in the Rhône-Alpes area between 2000 and 2005. Results: 140 patients satisfied inclusion criteria and were selected. The majority of 13–25 year old patients were treated in paediatric units. Joint management resulted in a higher rate of discussion in multidisciplinary tumour board, inclusion in clinical trials, and fertility preservation. Non-compliance with guidelines was observed in 65% of cases. Overall compliance was not reported to correlate to survival. Compliance of radiotherapy with CPG's seemed associated with a better prognosis for OS (HR = 0.20, 95% CI = [0.10–0.40]; p < 0.0001) and RFS (HR = 0.18, 95% CI = [0.09–0.37; p < 0.0001) as well as compliance of surgery for OS (HR = 0.43, 95% CI = [0.23–0.81]; p = 0.01). Multivariate Cox regression analysis revealed other independent predictors of OS like age at diagnosis, stage and histological subtype. Conclusions: Management of AYA in joint units seems to improve the quality of care. Compliance of surgery and radiotherapy with CGP's seems to improve survival.